Kajian antropologi sastra pedagogis pada novel Sokola Rimba karya Butet Manurung - Purwati Anggraini; Suyatno Suyatno; Tengsoe Tjahjono; Joko Widodo (Universitas Mulawarman, 2023)
The research aims to describe (1) the main character's adaptation to orang rimba culture; (2) the main character's steps in providing education to the orang rimba in the